GROUND PENETRATING RADAR (GPR) SURVEY ON THE LAVA FLOW IN THE SUBANG AREA, WEST JAVA PROVINCE, INDONESIA - -, Hendarmawan (Bulletin of Scientific Contribution, 2010)
Most hydrogeologist often meet the difficulties for exploration on tle lava flow when groundwater flow within that channel not emerging or no sputed on the surface. While, in other view, depending on frequency, GPR can resolve objects down to the size of a few meters or even centimeters, and this geophysical reflection method with the highest resolving power (GPR) is also as well established tool for geophysical investigations of the shallow subsurface. Thus, it is not surprising if this approach is used at lava flow terrain, in the Subang area. The tim can directly recognized the secondary permeable zone to recommendate the icline drilling with high accurate. Therefore, in this case, the extra effort and cost involved exceed the maksimum benefits or effisien.